A study on the genus Lagria from China with one new species and new distributional records (Coleoptera: Lagriinae) - Zhou, Yong; Chen, Bin (Zootaxa, 2023)
The species of the genus Lagria Fabricius, 1775 from China are reviewed with a total of 8 species recorded in this paper. One new species, Lagria (Lagria) medogensis sp. nov. is described from Tibet, China. Four species are newly recorded from China, Lagria (Ammocera) bhutanicola Merkl, 2019, L. (Am.) unicolor Borchmann, 1941, L. (L.) indicola Bates, 1879, and L. (L.) wanduensis Merkl, 2019. The Chinese provincial distribution records for three species are updated, L. (L.) ignota (Borchmann, 1941), L. (L.) nigricollis Hope, 1843, and L. (L.) oharai Masumoto, 1988. Intraspecific variability for L. (Am.) bhutanicola and similarity of color patterns among Ammocera species are discussed. L. (L.) indicola is redescribed and illustrated.